Comparative analysis of thermophysical properties of Al2O3 and SiO2 nanofluids / Saifuddin Khalid ... [et al.] - Khalid, Saifuddin; Zakaria, Irnie Azlin; Wan Mohamed, Wan Ahmad Najmi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
Considered, as one of the breakthrough in 21th century, Polymer Electrolyte Membrane Fuel Cell (PEMFC) is seen as one of the favourable alternative energy to internal combustion engine (ICE). However, the sensitivity of the membrane operation needs to be taken care of efficiently in order to ensure optimum performance of its power generation. The addition of nano-sized particles dispersed in water as base liquid has dramatically altered the thermo-physical property of the base coolant especially in heat transfer improvement. In this study, Al2O3 and SiO2 nanofluids with base fluid water were analysed in terms of critical thermo-physical properties for PEMFC application are experimentally studied. This covers thermal conductivity, dynamic viscosity and electrical conductivity properties. These nanofluids with low concentration of 0.1, 0.3 and 0.5 % volume is used in the study due to the limitation of low electrical conductivity limit for PEMFC in order to avoid electrical leakage to the coolant which will in effect causes a decrease the power generation. The 4.19 % and 1.42 % of improvement is shown in 0.5 % volume concentration of Al2O3 and SiO2 nanofluids in water respectively for thermal conductivity is recorded. However, the improvement also accompanied by viscosity and electrical conductivity increment in Al2O3 and SiO2 nanofluids as compared to base fluid water.